Digital Mammogram Segmentation and Abnormal Masses Detection System - Sahakyan, Armen (Mathematical Problems of Computer Science, 2021)
Digital Mammogram has emerged as the most popular screening technique for early detection of Breast Cancer and other abnormalities. Raw digital mammograms are medical images that are difficult to interpret so we need to develop Computer Aided Diagnosis (CAD) systems that will improve detection of abnormalities in mammogram images. Extraction of the breast region by delineation of the breast contour allows the search for abnormalities to be limited to the region of the breast. We need to perform essential pre-processing steps to suppress artifacts, enhance the breast region and then extract breast region by the process of segmentation. In this paper we present an automated system for detection of abnormal masses by anatomical segmentation of Breast Region of Interest (ROI).